Hotspots and frontiers of the relationship between gastric cancer and cancer-associated fibroblasts: a bibliometric analysis - Hu, Xiangcheng; Ren, Lingling; Zhu, Shuyuan; Shen, Haiping; Qian, Chengyong; Chen, Guanglan; Chen, Fangling (Frontiers in Oncology, 2025)
BackgroundCancer-Associated Fibroblasts (CAFs) are pivotal stromal constituents within the Tumor Microenvironment (TME), characterized by marked heterogeneity and plasticity. Over the past two decades, a notable association between Gastric Cancer (GC) and CAFs has been established. Despite this, there remains a paucity of comprehensive data to guide researchers in understanding the prevalence and potential research trajectories concerning GC and CAFs.MethodsThis study conducted an extensive literature search within the Web of Science Core Collection database from January 1, 2003, to December 31, 2023. Bibliometric analysis and visualization were performed using VOSviewer, CiteSpace, R software, and Microsoft Excel.ResultsA total of 1170 articles were included. These articles were disseminated across 200 journals and incorporated 1800 distinct keywords. A notable surge in publications has been observed from 2011 to 2023. China emerged as the leading contributor to both article count and citations. Prominent research institutions in this domain include Osaka City University, Shanghai Jiaotong University, and National Cancer Research Center Hospital. Notable researchers, such as Masakazu Yashiro and Kosei Hirakawa from Osaka City University and Zhenggang Zhu from Shanghai Jiaotong University, were among the most productive and highly cited authors. FRONTIERS IN ONCOLOGY boasts the highest number of publications, whereas ONCOGENE ranks as the most cited journal. The primary research foci within the realm of CAFs and GC encompass the impact of CAFs on GC cell proliferation, angiogenesis, invasion, metastasis, epithelial-mesenchymal transition, immunosuppression, drug resistance, and the interplay between CAFs and GC.ConclusionUsing bibliometric analysis, this study presents a panoramic view of the research landscape of CAFs and GC from 2003 to 2023. It highlights prominent research areas and anticipates future directions with the aim of offering valuable insights and strategic recommendations for future endeavors in this field.